Efektifitas Pemberian Terapi Relaksasi Genggam Jari Terhadap Tekanan Darah Pada Pra Lansia Penderita Hipertensi - Firdaus, Tiara Nurannisa; Hoedaya, Ahmad Purnama; Inriyana, Ria (Jurnal Keperawatan Florence Nightingale, 2024)
Hypertension remains a major challenge worldwide, both in developed and developing countries, and is the leading contributor to non-communicable disease-related deaths. The aim of this study is to determine the effectiveness of finger grip relaxation therapy on blood pressure in pre-elderly individuals with hypertension in Licin Village. The research employs a quantitative method with a Pre-Experimental One Group Pre-post test design. It was conducted by first observing the variables before the intervention, and then measuring them again after the intervention using a sphygmomanometer. The sample was selected using purposive sampling, resulting in 10 respondents who met the study's inclusion and exclusion criteria. The results showed that the average systolic blood pressure decreased by 10.00 mmHg and diastolic blood pressure decreased by 5.00 mmHg after the intervention. Based on the t-Test, a significant value of 0.000 was obtained for systolic blood pressure and 0.008 for diastolic blood pressure, leading to the conclusion that finger grip relaxation therapy effectively lowers blood pressure in pre-elderly individuals with hypertension in Licin Village. It is hoped that respondents will continue to practice finger grip relaxation therapy in accordance with the guidelines provided during the research, namely in a relaxed state while taking deep breaths twice a day in the morning and evening for five consecutive days.